Draft genome sequence of the extended-spectrum -lactamase-producing escherichia coli isolate INF13/18/A, recovered from Kelantan, Malaysia - Wan Makhtar, Wan Ratmaazila; Mohd Azlan, Mawaddah; Hassan, Nor Haslizai; Aziah, Ismail; Samsulrizal, Nurul Hidayah; Yusof, Nik Yusnoraini (American Society for Microbiology, 2020)
We describe here the draft genome sequence and basic characteristics of Escherichia coli isolate INF13/18/A, which was isolated from Universiti Sains Malaysia (USM) Hospital. This isolate was identified as an extended-spectrum -lactamaseproducing Escherichia coli strain harboring the antimicrobial resistance genes TEM, CTX-M-1, and CTX-M-9.